Cytotoxic and Antioxidant Compounds from the Stem Bark of Goniothalamus tapisoides Mat Salleh - Rosalind Pei Theng, Kim; Vicky, Bihud; Khalit, Mohamad; Kok Hoong, Leong; Jamaludin, Mohamad; Fasihuddin Badruddin, Ahmad; Hazrina, Hazni; Noraini, Kasim; Siti Nadiah, Abdul Halim; Khalijah, Awang (Molecules, 2012)
Eleven compounds: goniomicin A (1), goniomicin B (2), goniomicin C (3), goniomicin D (4), tapisoidin (5), goniothalamin (6), 9 deoxygoniopypyrone (7), pterodondiol (8), liriodenine (9), benzamide (10) and cinnamic acid (11), were isolated from the stem bark of Goniothalamus tapisoides. All compounds were identified by spectroscopic analysis and, for known compounds, by comparison with published data. Goniothalamin (6) exhibited mild cytotoxic activity towards a colon cancer cell line (HT-29), with an IC50 value of 64.17 ± 5.60 µM. Goniomicin B (2) give the highest antioxidant activity in the DPPH assay among all compounds tested, with an IC50 of 0.207 µM.